ATUNA RAFIN. versus CYCLANDROPHORA HASSK. (Rosaceae-Chrysobalanoideae) - a. j. g. h. kostermans (REINWARDTIA, 1969)
Atuna Rafinesque(Sylva Tellur.153. 1838)with a single species Atuna ra-cemosa Rafin. has priority over Cyclandrophora Hasskarl (in Flora 25(2), Beibl. 1: 47. 1842) and as it has been described properly it has precedence over Cyclandrophora. I formerly (in Candollea 20: 118. 1965) preferred to reinstate Cyclandrophora as there is a generic name Atunus [Rumph.] Lamarck 1797, a synonym of Heritiera Dryander (Sterculiaceae). After sounding out some experts in this matter,it has become evident, that the chances to conserve Cyclandrophora against Atuna are slight and hence I give here the new combinations of the species of this genus.